(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The integration of Artificial Intelligence (AI) into Regulatory Technology (RegTech) has emerged as a transformative force in enhancing economic efficiency and reducing compliance costs within financial markets. As regulatory frameworks become increasingly complex and financial transactions grow in volume and speed, traditional compliance processes based on manual reviews and static rule-based systems have proven insufficient, costly, and prone to error. AI-driven RegTech solutions address these challenges by leveraging machine learning, natural language processing, and data analytics to automate and optimize key compliance functions, including regulatory reporting, transaction monitoring, Know Your Customer (KYC) procedures, and anti-money laundering (AML) measures. AI-powered RegTech tools significantly reduce operational costs by automating labor-intensive processes, minimizing human errors, and improving the accuracy and speed of regulatory reporting. For example, AI systems can detect suspicious transactions, flag potential fraud, and ensure compliance with evolving regulatory requirements in real time. This not only enhances financial institutions’ ability to meet compliance obligations but also frees up human resources for higher-value tasks. Moreover, AI improves the detection of complex financial crimes through adaptive learning, reducing false positives and enhancing overall risk management. Regulatory authorities are also adopting AI tools to improve market surveillance, detect systemic risks, and ensure the integrity of financial systems more efficiently. While initial investments in AI-driven RegTech solutions can be significant, the long-term benefits in terms of cost reduction, improved compliance, and risk mitigation far outweigh the challenges. As financial markets become more digitized and interconnected, AI in RegTech is expected to play an increasingly central role in building resilient, efficient, and trustworthy financial ecosystems, fostering both economic growth and regulatory integrity.